Dynamiques sectorielles et emploi au Maroc - Sandra Palméro; Nathalie Roux (L’Année du Maghreb)
Over 10 years after Barcelona, the effects of economic openness in Mediterranean countries are not credible in terms of economic growth and employment dynamics. The purpose of our article is to identify the sectors likely to create employment and wealth in Morocco and to assess whether specialization choices can foster long-term growth and absorb excess labor force. First, we analyzed the potential for employment in economic sectors, especially in manufacturing industries between 1985 and 2001. Subsequently, we evaluated the impact of trade openness and specialization on net employment creation through both an empirical study and an econometric analysis. Our results shed a new light on traditional conclusions, which usually present a positive impact of economic openness on employment.